HOT TOPICS AND RESEARCH TRENDS IN THE APPLICATION OF ARTIFICIAL INTELLIGENCE IN SMART MANUFACTURING - Liu Yonggang; Hapini Awang; Nur Suhaili Mansor; Huda Ibrahim (PT Altin Riset Publishing, 2026)
With the advancement of Industry 4.0, artificial intelligence that integrates Internet of Things (IoT), big data (BD), edge computing (EC), digital twins, haptic feedback, and other technologies is penetrating various aspects of smart manufacturing, such as predictive maintenance, material design, automatic fault detection, and so on. Based on sampling data extracted from Scopus database between 1986 and 2025, this study employs a bibliometric analysis method to systematically analyse research trends, knowledge structures, and future directions in the field of artificial intelligence and smart manufacturing. The results show that this cross-disciplinary research between artificial intelligence and smart manufacturing has witnessed significant upward growth in recent years, especially since 2017. The top 10 most cited documents, most related documents, some productive authors, and high-frequency keywords have been identified. This study not only helps researchers comprehensively grasp the development trajectory but also provides directional guidance and knowledge map support for subsequent research.